Assessing Agency Theory and Solutions on the Financing of Revenue Sharing Systems in Islamic Banking - Nur Anisa Setyaningrum; M. Nur Kholis Setiawan; Siti Maghfiroh; Saiful Ansori (Ijtimā'`iyya: Journal of Muslim Society Research, 2022)
The dynamics of business development in Indonesia from time to time are increasingly complex. When in the past businesses were run by individuals or several parties and with a simple structure, but today has developed far in complex business entities, structured management and larger capital. One of the basic assumptions in accounting, the economic entity, states that a company is an independent economic entity that requires separation between the owner (owner) and the party running the business (management). Or common with the mention of agents and principals. The method used in this research is library research with qualitative descriptive analysis, information is taken from a number of references. The conclusion in this study is that the theory of agency ideally presents as a bridge of communication between agents and principals, but in practice problems and conflicts often arise. What happens, on one side the agent knows more about business information than the principal, for that if it does not have an honest sense of customer / agent can act moral hazard. Solutions in the agency's problems can be minimized by monitoring, bonding, and screening measures.